Penguasaan Harta Kekayaan Yayasan oleh Ahli Waris Pendiri Yayasan - Jannah, Mustahul; Tolo, Suriani BT.; Fitriadi, Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2023)
This research aims to find and analyze the legal status of the foundation's assets controlled by the heirs of the foundation founder and analyze the role of the government in supervising a foundation. This research uses normative juridical approaches with data collection method in the form of library research. The results of the study show that: first, the foundation's assets that are personally controlled by the heirs of the founder of the foundation include unlawful acts that can be held civilly liable and can be prosecuted criminally. The assets of the foundation cannot be transferred or controlled personally because the legal entity of the foundation is the owner of the community based on the theory of legal entity; second, the role of the government in supervising the foundation based on the authority by legislation through the Ministry of Law, Human Rights and Human Rights (Kemenkumham) and the Minister of Social Affairs through the Social Service.